2018
DOI: 10.4236/jmp.2018.95058
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Characteristics of Dust Acoustic Solitary Waves and Dust Acoustic Shock Waves in Electron Free Dusty Space Plasma

Abstract: A theoretical investigation has been done for the study of dust acoustic solitary waves and dust acoustic shock waves propagating in an unmagnetized, collisionless Lorentzian dusty plasma considering adiabatic and non-adiabatic dust charge variation. Plasma under consideration is composed of inertialess Lorentzian positive and negative ions along with inertial positively charged dust grains. Such dust grains are charged by the flow of positive ion and negative ion current over the grain surface. Adiabatic grai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…A study of the characteristics of freak waves in dusty plasma containing two temperatures ions is presented in [361], by modulating the KP equation to infer the nonlinear Schrdinger equation (NLSE). Nonlinear propagation of dust-acoustic (DA) solitary waves [359,368] in a three-component unmagnetized dusty plasma consisting of Maxwellian electrons, vortex-like (trapped) ions and arbitrarily charged cold mobile dust rain, is investigated in [369]. It is demonstrated that the dynamics of small but finite amplitude DA waves is regulated by a nonlinear equation of modified Korteweg-de Vries (mK-dV) type.…”
Section: Regions Of Single Particle Confinementmentioning
confidence: 99%
“…A study of the characteristics of freak waves in dusty plasma containing two temperatures ions is presented in [361], by modulating the KP equation to infer the nonlinear Schrdinger equation (NLSE). Nonlinear propagation of dust-acoustic (DA) solitary waves [359,368] in a three-component unmagnetized dusty plasma consisting of Maxwellian electrons, vortex-like (trapped) ions and arbitrarily charged cold mobile dust rain, is investigated in [369]. It is demonstrated that the dynamics of small but finite amplitude DA waves is regulated by a nonlinear equation of modified Korteweg-de Vries (mK-dV) type.…”
Section: Regions Of Single Particle Confinementmentioning
confidence: 99%
“…Both theoretical and experimental study of shock waves has been found in recent years [18][19][20][21]. In the case of the production of shock waves in dusty plasma, there exists a good number of theoretical and experimental works [21][22][23][24]. Shock waves can generally be produced in plasma if there is a dissipative force present in the plasma [25].…”
Section: Introductionmentioning
confidence: 99%